Mediasi Penal Sebagai Alternatif Dalam Penyelesaian Perkara Pidana Dalam Sistem Peradilan Pidana - Insan Pribadi; Aris Setyo Nugroho (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Penal mediation is a form of criminal case resolution outside of formal judicial mechanisms, emphasizing an agreement between the perpetrator and victim facilitated by a neutral third party. This approach aligns with the principles of restorative justice, which aim to restore victims' losses, improve social relationships, and avoid the negative impacts of conventional criminal justice. In the Indonesian criminal justice system, penal mediation is beginning to gain attention through regulations and policies. In practice, law enforcement faces numerous challenges and efforts in implementing restorative justice, including limitations in its application to certain crimes and the risk of abuse of authority. This confirms that penal mediation has great potential as a humane and efficient instrument in law enforcement, but requires a stronger legal framework, strict oversight, and education for both law enforcement officials and the public